The evidence supporting educational videos for patients and caregivers receiving hospice and palliative care: A systematic review. Issue 9 (September 2020) - Cruz-Oliver, Dulce M.; Pacheco Rueda, Angel; Viera-Ortiz, Liliana; Washington, Karla T.; Oliver, Debra Parker
Highlights: Video education in hospice and palliative care (HPC) has been understudied. The evidence supports the use of video education in hospice and palliative care. Video interventions have positive impact on preferences and advance care planning. Videos are a promising tool for education and communication enhancement in HPC. Abstract: Objective: The purpose of this study is to explore the evidence surrounding educational videos for patients and family caregivers in hospice and palliative care. We ask three research questions: 1. What is the evidence for video interventions? 2. What is the quality of the evidence behind video interventions? 3. What are the outcomes of video interventions? Methods: The study is a systematic review, following Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. Researchers systematically searched five databases for experimental and observational studies on the evidence supporting video education for hospice and palliative care patients and caregivers, published in 1969–2019. Results: The review identified 31 relevant articles with moderate-high quality of evidence. Most studies were experimental (74 %), came from the United States (84 %) and had a mean sample size of 139 participants. Studies showed that video interventions positively affect preferences of care and advance care planning, provide emotional support, and serve as decision and information aids. Conclusion: A strong body of evidence has emerged for video education interventions in hospice and palliative care. Additional research assessing video interventions' impact on clinical outcomes is needed. Practice implications: Videos are a promising tool for patient and family education in hospice and palliative care.